Sodium chloride against Dawestrema cycloancistrium in juvenile Arapaima gigas - Affonso, Elizabeth Gusmão; Queiroz, Marieta Nascimento; Ono, Eduardo Akifumi; Porto, Sanny Maria de Andrade; Claudiano, Gustavo da Silva (Aquaculture International, 2022)
The aim of the present study was to assess the use of sodium chloride (NaCl) against monogenoid trematodes infestations in pirarucu (Arapaima gigas). Two assays were conducted with pirarucu juveniles, the first comprising an in vitro exposure to 8, 9, 10, and 11 g·L−1 NaCl and the second, in vivo exposure test to NaCl at the same concentrations. The best in vitro results were observed for 1-h exposures at 9, 10, and 11 g·L−1 NaCl, resulting in 60% and 100% parasite mortality, respectively. In vivo exposures to 8 and 10 g·L−1 NaCl were 36 and 22% efficient, respectively, following 2 h of exposure, with no mortality. Some dose-dependent changes were observed in exposed fish, such as decreased hemoglobin and MCHC values at the highest NaCl concentration compared to the other NaCl concentrations and the control group. Most frequent gill tissue alterations observed were capillary dilatation and mucus secretions compared to the control group at the highest NaCl concentrations (10 and 11 g·L−1). Decreased mean (p < 0.05) water pH values and increased mean electrical conductivity were noted compared to the control group. In conclusion, our findings suggest that NaCl exhibits low toxicity toward pirarucu without physiological alterations and anthelmintic activity to the monogenoid directly influenced by exposure time and concentration. Moreover, 100% of the monogenoids present in the gills of the fish were identified as Dawestrema cycloancistrium.
Keywords: Biochemical; Parasitic diseases; Monogenoids; Gills; Histological analysis